Garuda in Southeast Asia’s Contested Waters: Indonesia dan Dinamika Keamanan Maritim Asia Tenggara - Indra Kusumawardhana; Frieska Haridha; Innesia Ma’sumah (Indonesian Perspective, 2020)
Indonesia’s strategic agenda to become the Global Maritime Fulcrum creates the discourse related to its existence in the context of maritime security in Southeast Asia. The emergence of Indonesia’s political realism to maintain the sovereignty of its waters has fueled various maritime insecurity problems that have occurred in Indonesian waters so far. Drawing from abovementioned context, this paper provides an analysis related to the various dynamics, challenges and issues of maritime security in Southeast Asia that surrounds Indonesia’s Global Maritime Fulcrum. Using traditional and non-traditional security study approaches in understanding maritime security, this paper examines various maritime insecurity issues faced by Indonesia, especially in the context of the Global Maritime Fulcrum agenda.